2013
DOI: 10.18046/syt.v11i26.1626
|View full text |Cite
|
Sign up to set email alerts
|

A review of Lego Mindstorms robotics platform for educational and research applications

Abstract: ResumenLa robótica es considerada como una de las áreas de gran interés de la ciencia y la tecnología de hoy en día. La robotización, es decir, los sistemas automatizados, se encuentran en casi todos los sectores de la sociedad. En la industria, los robots son utilizados para soldar, transportar, montar y pintar piezas. En medicina, robots sofisticados ayudan a llevar a cabo cirugías complejas. En el sector militar, los robots son usados para explorar áreas hostiles. Por tal motivo, la robótica móvil y los sis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In [47], a study of the possibilities of using Lego Mindstorm for teaching can be found, as well as the importance and versatility that the modularity of the kit provides. It allows physically modifying the robots with assembling pieces and to modify their behaviour based on algorithms specified by visual programming or text based programming.…”
mentioning
confidence: 99%
“…In [47], a study of the possibilities of using Lego Mindstorm for teaching can be found, as well as the importance and versatility that the modularity of the kit provides. It allows physically modifying the robots with assembling pieces and to modify their behaviour based on algorithms specified by visual programming or text based programming.…”
mentioning
confidence: 99%